Communication—Electrochemical Investigation of Plate-Like Na2/3Fe1/2Mn1/2O2 for Sodium Ion Cathode. Issue 2 (1st January 2018) - Viswanatha, R.; Kishore, Brij; Bharath, U.; Munichandraiah, N.
Abstract : Sodium ion batteries with low cost and high capacities have attracted much attention. Herein, P2-type Na2/3 Fe1/2 Mn1/2 O2 is synthesized by self-combustion method and characterized for physicochemical and electrochemical properties. The XRD confirms that the sample is formed in a pure phase. Cyclic voltammograms of electrodes are characterized by two well-defined pairs of peaks corresponding to redox processes in two different stages. The electrochemical studies as a cathode for sodium ion batteries are investigated in the 1.5–4.2 V range using Na metal as anode. An initial discharge capacity of about 210 mAh g −1 is obtained at C/10 rate.